Did Sāmoa Have Intensive Agriculture in the Past? New Findings from LiDAR - Jackmond, Gregory; Fonotī, Dionne; Tautunu, Matiu Matāvai (Waka Kuaka, 2019)
During recent field survey work in Aleipata on the southeast coast of the Independent State of Samoa several new archaeological features have been discovered by a LiDAR-guided ground survey. The survey confirmed evidence from LiDAR images of a dense habitation zone from the coast to several kilometres inland with an extensive drainage system. We suggest that prior to the nineteenth century, when Sāmoan political organisation was first described, the extent and interconnectivity of the channels suggest that a larger population, a more intensive organisation of labour and resources for agricultural production, and a more extensive system of political authority existed.